(untitled) - Stallings, William (Englewood Cliffs, N.J., 1995)
Comprehensive in approach, this introduction to network and internetwork security provides a tutorial survey of network security technology, discusses the standards that are being developed for security in an internetworking environment, and explores the practical issues involved in developing security applications.
Keywords: Computer networks,Computer security,Mạng máy tính,Bảo mật máy tính; Security measures,Biện pháp an ninh